Perlakuan akuntansi biaya pengembangan sumber daya manusia pada perusahaan daerah air minum kota samarinda - Rani Novita Sari (Faculty of Economics and Business Mulawarman University, 2016)
This research was conducted in order to view and analyze the process of recording and reporting done by the Regional Water Company Samarinda city in terms of the recognition of human resources owned, particularly in the register and the recognition of human resources in the preparation and financial reporting which are made. With reference to the Financial Accounting Satandar particularly concerning intangible assets, which are arranged in SAK ETAP chapter 16 on intangible assets. Intangible assets into a discourse for an organization in a report on human resources held to be reported in financial reporting made by the organization. This research was conducted with the concept of human values (human value) is derived from the theory of economic value (general human value theory). In this case there are two theories, namely Falmholtz's Theory, and Likert and Bowers Theory. SAK ETAP especially chapter 16 on intangible assets is used as a reference to see if the Regional Water Company Samarinda city has used SAK ETAP chapter 16 as a reference in preparing its financial statements in the report, especially its human resources. This research was conducted with a direct view of the research object in this case Local water company Samarinda with the aim to see whether in the preparation and the recognition of human resources in the financial statements in accordance with GAAP or not ETAP 16 existing chapters. The research method is descriptive. From the analysis and observations made, the result that the Regional Water Company of Samarinda in reporting and the preparation of financial statements in particular the recognition of human resources has been referred to SAK ETAP chapter 16. Dari hasil analisis dan observasi yang dilakukan, diperoleh hasil bahwa Perusahaan Daerah Air Minum Kota Samarinda dalam melakukan pelaporan dan penyusunan laporan keuangan khususnya terhadap pengakuan akan sumber daya manusia telah mengacu kepada SAK ETAP bab 16. In the preparation and financial reporting standards that are a reference among IAS and SAK ETAP, especially for intangible assets under SFAS numbers in SFAS No. 19 and for SAK ETAP regulated in Chapter 16. For the Regional Water Company Minun Samarinda own use SAK ETAP chapter 16 in recognizing and reporting on its human resources. Keyword: SAK ETAP, PDAM, Intangible Assets